Case workers in family court: A therapeutic jurisprudence analysis. (September 2016) - Lens, Vicki; Katz, Colleen Cary; Suarez, Kimberly Spencer
Abstract: This study explores interactions between judges and caseworkers in child maltreatment cases. We examined the extent to which judges demonstrated therapeutic jurisprudence principles (TJ) in their courtroom interactions in light of past findings linking such practices with positive outcomes. Ninety-four child maltreatment proceedings were observed over a one-year period between 2012 and 2013. We found that while some judges created respectful, empathetic, and supportive environments that included caseworkers, other interactions were more negative. Although caseworkers had the most knowledge of, and experience with families, their participation was limited, and conversations were often directed through the attorneys. Shaming rituals also occurred, with judges criticizing workers for the quality of their work, the slowness of the bureaucracy, and other deficiencies. The findings highlight the importance of applying the principles of TJ to all court actors, especially in the family court milieu, where courtrooms are populated by a team of professionals who share the common goal of rehabilitating families when appropriate. Highlights: We observe interactions between Family Court judges and child welfare workers in child protection cases. We use the principles of therapeutic jurisprudence to delineate positive encounters from negative ones. Some judges were less inclusive of caseworkers than other judges, limiting their participation and communicating primarily through the attorneys. Some judges responded negatively to caseworkers, criticizing their work, and identifying other deficiencies. A more inclusive, respectful and participatory approach would better help the Family Court rehabilitate families.